The Importance of School Pedagogical and Social Climate to Students' Unauthorized Absenteeism – a Multilevel Study of 101 Swedish Schools. Issue 1 (2nd January 2022) - Karlberg, Martin; Klang, Nina; Andersson, Filip; Hancock, Kirsten; Ferrer-Wreder, Laura; Kearney, Christopher; Galanti, Maria Rosaria
ABSTRACT: While individual and family factors behind students' school absenteeism are well-researched, fewer studies have addressed school climate factors. This study investigated the association between school climate in Swedish schools and students' absenteeism. A multi-informant survey of school climate was conducted in 101 schools and analysed in relation to the history of absenteeism of 2770 students attending those schools in the 7th grade at inception, with follow-up until completion of the compulsory school (9th grade). Data on absenteeism was extracted from schools' registers. Student (but not teacher) positive ratings of school climate were associated with lower absenteeism between the age of 13 and the age of 16. The associations between student rated school climate and absenteeism appeared stronger among students with highly educated parents.